2006
DOI: 10.1136/jnnp.2005.082362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neck flexion on F wave, somatosensory evoked potentials, and magnetic resonance imaging in Hirayama disease

Abstract: Background: Flexion myelopathy is one of the suggested mechanism for Hirayama disease (HD) but simultaneous radiological and neurophysiological evaluation is lacking. This study therefore evaluates the effect of neck flexion in HD using somatosensory evoked potentials (SEPs), F waves, and magnetic resonance imaging (MRI). Method: Eight HD patients and seven matched controls were subjected to median and ulnar F wave (minimal latency, FM ratio, persistence, and chronodispersion), and SEPs evaluating N9, N13, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Although we noted this phenomenon in some of our patients it did not predict disease progression. In our population SEP's studies were normal, as has been reported in Asian patients, [12,51] although mild changes were described in one study [52]. EMG abnormalities beyond the territory of clinically affected muscles are often suggested as predictive of progression to clinical involvement of other limbs.…”
Section: Discussionmentioning
confidence: 49%
“…Although we noted this phenomenon in some of our patients it did not predict disease progression. In our population SEP's studies were normal, as has been reported in Asian patients, [12,51] although mild changes were described in one study [52]. EMG abnormalities beyond the territory of clinically affected muscles are often suggested as predictive of progression to clinical involvement of other limbs.…”
Section: Discussionmentioning
confidence: 49%
“…Because of chronic denervation there may be prolongation of latency, decline in persistence, and reduction in amplitude; however depending on reinnervation, the amplitudes may increase. In patients with severe wasting, the F wave may become unrecordable [36]. …”
Section: Electrophysiologymentioning
confidence: 99%
“…EMG typically shows the presence of neurogenic lesions in all affected muscles with spontaneous potentials, a prolonged duration or augmentation of amplitude in motor unit potentials, or an incomplete pattern of recruitment. 5,[18][19][20]28 Electrophysiological studies performed during neck flexion failed to prove abnormalities related to neck posture, 20 although those studies were performed at the plateau phase of the disease, and there was no mention of how long flexion was maintained.…”
Section: Discussionmentioning
confidence: 99%